Specific Features And Development Trends Of The Activities Of The Infrastructure Of The Insurance Market Of Uzbekistan - Khamidovich, Tursunov Shukhrat; Ikramovich, Roʻziyev Zafar; Rashidovich, Murtozayev Nurbek; Mirjamilovich, Iskandarov Abdurasul (The journal of contemporary issues in business and government, 2021)
In a market economy, insurance has a special role to play in ensuring the continuity of production and protecting the population from accidents. Insurance is an important economic pillar of the transition to a market economy as one of the necessary elements of production. The insurance market provides financial assistance in protecting almost all forms of property from natural disasters, compensation for damage caused to people as a result of various disasters. The study of methods of its organization and development on a large scale in the same insurance market, including the organization of the activities of professional participants who effectively participate in it, demonstrates the relevance of the topic of the article. In addition, the article is aimed at studying the current state of the infrastructure of the insurance market in Uzbekistan at the current stage of development, the development of scientific and practical proposals for its development based on the analysis.